(untitled) (Research, Society and Development, 2021)
Handling of pigs under hot weather conditions face a critical challenge in meeting thermal comfort and animal welfare standards. Moreover, climate variation affects production and pre-slaughter logistics. This study assesses the thermal comfort of pigs during pre-slaughter procedures under different weather conditions. The case study was conducted at two commercial pig farms in Southeastern Brazil. The bioclimatic index more accurately indicated the pigs’ thermal comfort than the temperature-humidity index. The length of the transportation journey critically affected the pigs’ thermal comfort, as shown by the rise in pigs’ skin temperature (1.56 °C and 1.64 °C on pigs from Farm 2 and Farm 1, respectively). The pigs reached the critical upper limit of the thermoneutral zone under hot weather conditions. Adequate microclimate control during the pre-slaughter management procedures might improve pig welfare. To increase the animals’ thermal comfort, both farms should reschedule their transportation to a cooler time of the day. Both farms should also improve their pre-slaughter management processes by training workers to comply with animal welfare requirements and reduce loss.